Quantitative and qualitative comparison of single source dual-energy CT and 120 kVp CT for the assessment of pancreatic ductal adenocarcinoma - Bhosale, Priya (J Comput Assist Tomogr, 2015)
PURPOSE: To compare contrast-to-noise ratio (CNR) and signal-to-noise ratio (SNR) between pancreatic phase dual-energy computed tomography (DECT) and 120 kVp CT for pancreatic ductal adenocarcinoma (PDA). MATERIALS AND METHODS: 78 patients underwent multiphasic pancreatic imaging protocols for PDA (40, DECT and 38, 120 kVp CT [control]). Using pancreatic phase, CNR and SNR for PDA were obtained for DECT at monochromatic energies (ME) 50 through 80 keV, iodine material density images (MDI), and 120 kVp images. Using a 5 point scale (1=excellent and 5=markedly limited) images were qualitatively assessed by two radiologist in consensus for PDA detection, extension, vascular involvement, and noise. Wilcoxon signed-rank and 2-sample tests were used to compare the qualitative measures, CNR, SNR for DECT and 120 kVp images. Bonferroni correction was applied. RESULTS: Iodine MDI had significantly higher CNR and SNR for PDA than any ME images (p<.0001) and the 120 kVp images. Qualitatively 70 keV images were rated highest in the categories of tumor extension and vascular invasion and were similar to 120kVp images. CONCLUSION: Our results indicate that DECT improves PDA lesion conspicuity compared to routine 120 kVp CT which may allow for better detection of PDA.